AB1144 DAILY CLINICAL CARE OF PATIENTS WITH MUSCULOSKELETAL COMPLAINTS – HOW HELPFUL IS A TRIAGE SYSTEM FOR EARLY RECOGNITION OF INFLAMMATORY RHEUMATIC DISEASES?. (2nd June 2020) - Baraliakos, X.; Redeker, I.; Zacharopoulou, M.; Tsiami, S.; Tsiaousi, K.; Morzeck, D.; Braun, J.
Abstract : Background: Early diagnosis and treatment are important for the management of inflammatory rheumatic diseases (RMD). However, the availability of rheumatologists is limited in most European countries and selection strategies lack sensitivity and/or specificity. Objectives: To evaluate a triage strategy that offers the possibility to see patients within 4 weeks for short term appointments in order to check the probability of an inflammatory RMD and the necessity to further evaluate the patients in due time. Methods: Physician's and patient's information who called our tertiary rheumatology department´s outpatient clinic for a date in the triage system were included in this analysis. The time to first appointment as assessed by a nurse (Step 1), the short evaluation by a rheumatologist in the triage (Step 2) and the patient´s complaints and the diagnoses after an extensive diagnostic evaluation (Step 3) were documented. Results: In a period of 9 months in 2018, a total of 982 patients presented. A total of 62 patients (6.3%) were considered urgent (appointment within 3 days), while 240 (24.4%) were appointed within 4 weeks at Step 2. Of the former 46 (19.2%), and of the latter 151 patients (62.9%) were diagnosed with inflammatory RMD at Step 3. In total, 334 patients (34.0%) were diagnosed with inflammatory RMD at Step 3, including 126 with RA (37.7%), 71 with axSpA/PsA (21.3%), 95 with connective tissue disease/vasculitis (28.4%) and 20 with gout (6.0%). The diagnosis suspected in Step 2 was confirmed in Step 3 in 77.9% of cases. In 217 patients, the diagnosis suspected in Step 2 was not confirmed in Step 3. Of them, 34 (15.7%) had unclear findings at Step 2 but an inflammatory RMD was found at Step 3, while 148 (68.2%) had a suspected inflammatory RMD at Step 2 but this was not confirmed at Step 3. The most frequent musculoskeletal complaint at the time point of referral was pain in small peripheral joints (hands and/or feet) in 858 patients (87.4%), in large peripheral joints (knees, shoulders and/or hips) in 780 patients (79.4%) and back pain in 682 patients (69.5%). Fever, night sweats and unclear weight loss was reported by 50 patients (5.1%), while 210 patients (24.5%) presented with findings suspicious of inflammatory RMD such as elevated CRP of unclear origin, and 43 patients (4.8%) because of a threat of organ damage such as unclear elevation of creatinine, as reported by the referring physician. In addition, 167 patients (17.0%) had received glucocorticoids prior to referral, 87 (52.1%) of which finally did not receive the diagnosis of inflammatory RMD at Step 3, while 737 patients (75.1%) were receiving NSAIDs prior to referral. Conclusion: In this prospective evaluation of a triage system where all patients were pre-screened by a nurse and were seen within 4 weeks by a rheumatologist, clinical differentiation could be performed timely due to a successfully structured triage system. The initially suspected diagnosis was finally confirmed in ≥75% of cases, while ≥1/3 of patients had a definite inflammatory RMD. This work was supported by an unrestricted Grant from Abbvie Disclosure of Interests: Xenofon Baraliakos Grant/research support from: Grant/research support from: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Consultant of: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Speakers bureau: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Imke Redeker: None declared, Maria Zacharopoulou: None declared, Styliani Tsiami: None declared, Konstantia Tsiaousi: None declared, Doris Morzeck: None declared, Juergen Braun Grant/research support from: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, Eli Lilly and Company, Medac, MSD (Schering Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi- Aventis, and UCB Pharma, Consultant of: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Eli Lilly and Company, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis, and UCB Pharma, Speakers bureau: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Eli Lilly and Company, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis, and UCB Pharma